(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Rural market of India has a large potential stilluntapped. So it would be very vital to know about the customer behavior in sucha segment of the market as it would be of great help to the marketers tounderstand the consumer pattern in that niche. This study will also help todetermine the brand loyalty of the rural customer towards the various FMCGbrands and thus accordingly companies can build their strategy. The study wouldalso reveal about the problems faced by the rural customers with regard tobranded FMCG products which would again be very much crucial to know.